2019
DOI: 10.3390/app9234992
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Impacts of Climate Change on Eddy Meridional Moisture Transport in the Atmosphere

Abstract: Research findings suggest that water (hydrological) cycle of the earth intensifies in response to climate change, since the amount of water that evaporates from the ocean and land to the atmosphere and the total water content in the air will increase with temperature. In addition, climate change affects the large-scale atmospheric circulation by, for example, altering the characteristics of extratropical transient eddies (cyclones), which play a dominant role in the meridional transport of heat, moisture, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 86 publications
0
6
0
1
Order By: Relevance
“…In this case, the baroclinic instability is considered as an eigenvalue problem that is usually solved using the perturbation method, which admits a plane-wave solution. Then, it can be shown that the meridional heat flux due to transient eddies depends exponentially on the increments of unstable perturbations [62]. Let us explain this in more detail.…”
Section: Meridional Heat and Moisture Transport: Linear Approximationmentioning
confidence: 97%
See 4 more Smart Citations
“…In this case, the baroclinic instability is considered as an eigenvalue problem that is usually solved using the perturbation method, which admits a plane-wave solution. Then, it can be shown that the meridional heat flux due to transient eddies depends exponentially on the increments of unstable perturbations [62]. Let us explain this in more detail.…”
Section: Meridional Heat and Moisture Transport: Linear Approximationmentioning
confidence: 97%
“…Substituting the normal mode solution ( 7) into the linearized model equations, one can derive the system of algebraic equations that can be solved analytically with respect to phase velocity c. The increments of unstable waves, represented by χ k , are defined as χ k = kc i , where c i = m(c) is the imaginary part of the phase velocity. For the β-plane (Phillips) model, which is the classic model of baroclinic instability, the growth rate χ k is calculated as follows [57,62]:…”
Section: Meridional Heat and Moisture Transport: Linear Approximationmentioning
confidence: 99%
See 3 more Smart Citations